Deriving Optimal Competition in Infrastructure Procurement - Teo, P.; Bridge, A.; Love, Peter (2015)
Typically, only a limited number of consortiums are able to competitively bid for public private partnership (PPP) projects. Consequently, this may lead to oligopoly pricing constraints and ineffective competition, thus engendering ex ante market failure. In addressing this issue, this paper aims to determine the optimal number of bidders required to ensure a healthy level of competition is available to procure major infrastructure projects. The theories of structure-conduct-performance (SCP) paradigm; Game Theory and Auction Theory and transaction cost economics are reviewed and discussed and used to produce an optimal level of competition for major infrastructure procurement, that prevents market failure ex ante (lack of competition) and market failure ex post (due to asymmetric lock-in).